2023
DOI: 10.4314/jasem.v27i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Single and Competitive Removal of Pb(II) in the Presence of Ni(II) using Polyacrylamide Grafted Rice Husk

Abstract: In a quest to find efficient adsorbents for metal ions, studies on various adsorbents for metals have been of interest since the past several decades. The present study is focused on the removal of Pb (II) ions from aqueous solution using poly acrylamide grafted rice husk by batch studies. Industrial waste waters generally contain metals present as mixtures, therefore the effect of Ni (II) on the removal of Pb(II) from mixtures of Pb(II)+Ni(II) ions has also been investigated. The adsorbent has been prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…It can be appreciated that when hydrolyzed species appear in solution, nanometric precipitates, in our case, cover the "active" surface available for Pb(II) ions adsorption. The results are consistent with those found by Sumanjeet et al [56], Verma et al [57], and Ifijen et al [58]. Sajid et al observed the coating of sorbent with metal hydroxides and an increase in the time for sample filtration [59].…”
Section: Ph Effectsupporting
confidence: 91%
“…It can be appreciated that when hydrolyzed species appear in solution, nanometric precipitates, in our case, cover the "active" surface available for Pb(II) ions adsorption. The results are consistent with those found by Sumanjeet et al [56], Verma et al [57], and Ifijen et al [58]. Sajid et al observed the coating of sorbent with metal hydroxides and an increase in the time for sample filtration [59].…”
Section: Ph Effectsupporting
confidence: 91%